2018
DOI: 10.2503/hortj.okd-096
|View full text |Cite
|
Sign up to set email alerts
|

Development of DNA Markers Linked to Double-Flower and Hortensia Traits in <i>Hydrangea macrophylla</i> (Thunb.) Ser.

Abstract: Double flower and hortensia (mophead) hydrangea (Hydrangea macrophylla (Thunb.) Ser.) traits are recessively inherited. Cross breeding of these traits in hydrangea is difficult because it takes about two years from crossing to flowering. In this study, we aimed to obtain DNA linkage markers that would allow accelerated selection of these traits. We used next-generation sequencing to comprehensively collect DNA sequences from the 'Kirakiraboshi' with a double flower and lacecap inflorescence and the 'Frau Yoshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…Mophead inflorescence was reported to be a recessive characteristic controlled by a single recessive gene located on linkage group 4 8,50 . Even though little information is known about the physiological and genetic mechanisms causing the mophead phenotype, the GWAS and segregation of the discovered SNP in the F 2 population does support the hypothesis that the appearance of the mophead phenotype is a qualitative rather than a quantitative change in H. macrophylla, as proposed by Uemachi and Okumura 8 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mophead inflorescence was reported to be a recessive characteristic controlled by a single recessive gene located on linkage group 4 8,50 . Even though little information is known about the physiological and genetic mechanisms causing the mophead phenotype, the GWAS and segregation of the discovered SNP in the F 2 population does support the hypothesis that the appearance of the mophead phenotype is a qualitative rather than a quantitative change in H. macrophylla, as proposed by Uemachi and Okumura 8 .…”
Section: Discussionmentioning
confidence: 99%
“…An insertion of a long terminal repeat retrotransposon into the locus controlling inflorescence type was also proposed by the same research group through an observation of lacecap hydrangea cultivar mutation, but such a finding was not able to be connected to the current study due to limited genomic information. While genetic markers linked to inflorescence type in bigleaf hydrangea have been reported previously 46,50 , the single marker discovered and utilized herein has advantages for use in MAS. The previously published markers must be used in combination for marker-assisted selection while the SNP detailed here can be used alone.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that the double flower phenotype is a recessive trait controlled by a single major gene. 4 , 5 Suyama et al 4 found that crosses between the progeny of ‘Sumidanohanabi’ and the progeny of ‘Jogasaki’ produced only single flower descendants. Thus, it was also suggested that the genes controlling the double flower phenotype are different.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it was also suggested that the genes controlling the double flower phenotype are different. 4 We named the double flower locus d su as the locus controlling the double flower phenotype of ‘Sumidanohanabi’ and the double flower locus d jo as the locus controlling the double flower phenotype of ‘Jogasaki.’ Waki et al 5 identified d su on the genetic linkage map. They also found that the DNA marker STAB045 was the closest marker to d su and that STAB045 could help distinguish flower phenotypes with a high degree of agreement.…”
Section: Introductionmentioning
confidence: 99%
“…A phylogenetic tree of Hydrangea species was established to study the possibility of interspecific hybridization by using 13 highly polymorphic chloroplast markers (Mendoza et al, 2013). Recently, Waki et al (2018) screened 768 SSR primer pairs in 93 F 2 progeny to identify markers linked to double-flower and hortensia (mophead) traits in H. macrophylla; they found that both traits are each controlled by a single recessive gene. Many SSRs were developed through transcriptome sequencing and used for genetic mapping of powdery mildew resistance, remontancy, and flower type in hydrangea, but they were insufficient for linkage mapping due to the lack of marker density (Rinehart et al, 2018).…”
mentioning
confidence: 99%